1997
DOI: 10.3109/10715769709065790
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Electron Spin Resonance Signals in the Interaction of Dithiocarbamate-Fe(II) with Nitrogen Dioxide and Nitrite

Abstract: Whether dithiocarbamate-Fe(II) complexes used in the electron spin resonance (ESR) studies are specific for the detection of NO was investigated. It was found that the typical ESR signals of dithiocarbamate-Fe(II)-NO spin adducts appeared in the interaction of N-methyl-D-glucaminedithiocarbamate (MGD)-, bis(hydroxyethyl) dithiocarbamate (HED)- and diethyldithiocarbamate (DED)-Fe(II) complexes with the NO-derived nitrogen oxides, nitrogen dioxide (NO2) and nitrite ion (NO2-) in a prolonged incubation. Under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…This is consistent with findings in our laboratory that NOX-101 reduces the increase in plasma nitrate plus nitrite during cardiac allograft rejection [59]. We believe that the property of NOX-101 to scavenge NO is relatively specific as electron spin resonance spectroscopy confirms that similar derivatives bind nitrite and nitrogen dioxide with only 2±3 % efficiency and do not bind nitrate or peroxynitrite [60].…”
Section: Discussionsupporting
confidence: 80%
“…This is consistent with findings in our laboratory that NOX-101 reduces the increase in plasma nitrate plus nitrite during cardiac allograft rejection [59]. We believe that the property of NOX-101 to scavenge NO is relatively specific as electron spin resonance spectroscopy confirms that similar derivatives bind nitrite and nitrogen dioxide with only 2±3 % efficiency and do not bind nitrate or peroxynitrite [60].…”
Section: Discussionsupporting
confidence: 80%
“…This setup (Fig. 1A) was designed to isolate the reaction solution in the purging vessel from the spin trap and thus avoid any possible perturbation caused by the reaction of (MGD) with nitrite or with the enzyme (16,17). Samples from purging vessel 2 were aliquoted at desired times for EPR measurements.…”
Section: Methodsmentioning
confidence: 99%
“…However, Hiramoto et al [36] recently claimed that the signals of dithiocarbamate-Fee + -NO could be observed immediately after NO (1 mM) was mixed with MGD-Fe 2 + complex, and the signals increased with the NO concentration and prolonged incubation time. At the same time, Alexandre et al [37] also observed NO adduct signals derived from nitrite, the NO production from the reaction of nitrite disproportion could be increased 100-fold under acidic conditions, but under normal physiological conditions (pH 7.4) only low NO production occurred.…”
Section: Discussionmentioning
confidence: 99%